Common Skin Diseases in Children: Diagnosis and Management - Abeck, Dietrich; Burgdorf, Walter; Cremer, Hansjörg (Steinkopff, 2003)
Acne -- Alopecia Areata -- Arthropod Bite and Sting Reactions -- Atopic Dermatitis -- Burns and Sunburn -- Diaper Dermatitis -- Granuloma Annulare -- Herpes Simplex Virus Infections -- Impetigo -- Lice Infestations -- Lichen Sclerosus et Atrophicus -- Lyme Borreliosis -- Cutaneous Mastocytosis -- Molluscum Contagiosum -- Perioral Dermatitis -- Pityriasis Lichenoides -- Pityriasis Rosea -- Psoriasis -- Scabies -- Seborrheic Dermatitis -- Tinea Capitis -- Urticaria -- Varicella-Zoster Virus Infections -- Vascular Anomalies -- Viral Exanthems -- Warts -- Appendices.